Electrically active induced energy levels and metastability of B and N vacancy-complexes in 4H–SiC. (17th April 2018) - Igumbor, E; Olaniyan, O; Mapasha, R E; Danga, H T; Omotoso, E; Meyer, W E
Abstract: Electrically active induced energy levels in semiconductor devices could be beneficial to the discovery of an enhanced p or n -type semiconductor. Nitrogen (N) implanted into 4H–SiC is a high energy process that produced high defect concentrations which could be removed during dopant activation annealing. On the other hand, boron (B) substituted for silicon in SiC causes a reduction in the number of defects. This scenario leads to a decrease in the dielectric properties and induced deep donor and shallow acceptor levels. Complexes formed by the N, such as the nitrogen-vacancy centre, have been reported to play a significant role in the application of quantum bits. In this paper, results of charge states thermodynamic transition level of the N and B vacancy-complexes in 4H–SiC are presented. We explore complexes where substitutional N /N or B /B sits near a Si (V ) or C (V ) vacancy to form vacancy-complexes (N V, N V, N V, N V, B V, B V, B V and B V ). The energies of formation of the N related vacancy-complexes showed the N V to be energetically stable close to the valence band maximum in its double positive charge state. The N V is more energetically stable in the double negative charge state close to the conduction band minimum. The N V on the other hand, induced double donor level and the N V induced a double acceptor level. For B related complexes, the B V and B V were energetically stable in their single positive charge state close to the valence band maximum. As the Fermi energy is varied across the band gap, the neutral and single negative charge states of the B V become more stable at different energy levels. B and N related complexes exhibited charge state controlled metastability behaviour.